2010
DOI: 10.1111/j.1533-2500.2009.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Girdle Pain and Low Back Pain in Pregnancy: A Review

Abstract: Pregnancy-related pelvic girdle pain (PGP) and pregnancy-related low back pain (PLBP) are common problems with significant physical, psychological, and socioeconomic implications. There are several management options that are underutilized because of lack of comprehensive knowledge by health-care professionals and fear of harmful effects of treatment on the developing fetus. Interventions such as patient education, the use of pelvic belts, acupuncture, and aquatic and tailored postpartum exercises can be of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
262
0
41

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(307 citation statements)
references
References 90 publications
4
262
0
41
Order By: Relevance
“…1 Back pain in pregnancy is a health concern in terms of not just physical pain and disability but also psychological and socioeconomic consequences affecting the health of pregnant women. 5,8,[22][23][24] In this case study, the patient presented with moderate pain as reported by a high pain numerical value. She reported functional limitations impacting daily living activities in her pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…1 Back pain in pregnancy is a health concern in terms of not just physical pain and disability but also psychological and socioeconomic consequences affecting the health of pregnant women. 5,8,[22][23][24] In this case study, the patient presented with moderate pain as reported by a high pain numerical value. She reported functional limitations impacting daily living activities in her pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The other two tests, Gaenslen test and ASLR, were chosen because they are established in the literature on differential diagnosis of the lower back pain source with neural involvement (18). The last three tests are recommended by European community (20) and different authors (5,10,18,21) as the ODI. For the parametric data the Pearson correlation test was used and the level of significance was set at p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Vermani et al (10) reported that the pain lumbopelvic starts from 18 gestational weeks, and the highest intensities occur between the 24th to 36th week. Malmqvist et al (4) reported that most women who develop moderate to severe pain, had this symptom from the 20th gestational week.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have tried to identify the etiology and pathogenesis of PPGP, but it still remains unknown. Although individual factors such as: mechanical, metabolic, traumatic, hormonal and degenerative are described as potential causes of PPGP [7] recent literature suggests a combination of factors might better explain its underlying mechanism [1].…”
Section: Introductionmentioning
confidence: 99%
“…A combination of mechanical and hormonal changes experienced during pregnancy is often cited as a possible cause for this disorder [8][9][10]. During pregnancy, the gravid uterus load acting on the spine and pelvis increases considerably.…”
Section: Introductionmentioning
confidence: 99%